The bad ones - Albert, Melissa (Flatiron Books, 2024)
"In the course of a single winter's night, four people vanish without a trace across a small town. Nora's estranged best friend, Becca, is one of the lost. As Nora tries to untangle the truth of Becca's disappearance, she discovers a darkness in her town's past, as well as a string of coded messages Becca left for her to unravel. These clues lead Nora to a piece of local lore: a legendary goddess of forgotten origins who played a role in Nora and Becca's own childhood games..." --